Amino Acid Mutations in the NS4A Region of Hepatitis C Virus Contribute to Viral Replication and Infectious Virus Production - Murayama, Asako (J Virol, 2017)
Hepatitis C virus (HCV) strain JFH-1, which belongs to genotype 2a, replicates autonomously in cultured cells, whereas another genotype 2a strain, J6CF, does not. Previously, we found that replacement of the NS3 helicase and NS5B-to-3′X regions of J6CF with those of JFH-1 confers J6CF replication competence. In this study, we aimed to identify the minimum modifications within these genomic regions needed to establish replication-competent J6CF. We previously identified 4 mutations in the NS5B-to-3′X region that could be used instead of replacement of this region to confer J6CF replication competence. Here, we induced cell culture-adaptive mutations in J6CF by the long-term culture of J6CF/JFH-1 chimeras composed of JFH-1 NS5B-to-3′X or individual parts of this but not the NS3 helicase region. After 2 months of culture, efficient HCV replication and infectious virus production in chimeric RNA-transfected cells were observed, and several amino acid mutations in NS4A were identified in replicating HCV genomes. The introduction of NS4A mutations into the J6CF/JFH-1 chimeras enhanced viral replication and infectious virus production. Immunofluorescence microscopy demonstrated that some of these mutations altered the subcellular localization of the coexpressed NS3 protein and affected the interaction between NS3 and NS4A. Finally, introduction of the most effective NS4A mutation, A1680E, into J6CF contributed to its replication competence in cultured cells when introduced in conjunction with four previously identified adaptive mutations in the NS5B-to-3′X region. In conclusion, we identified an adaptive mutation in NS4A that confers J6CF replication competence when introduced in conjunction with 4 mutations in NS5B-to-3′X and established a replication-competent J6CF strain with minimum essential modifications in cultured cells. IMPORTANCE The HCV cell culture system using the JFH-1 strain and HuH-7 cells can be used to assess the complete HCV life cycle in cultured cells. This cell culture system has been used to develop direct-acting antivirals against HCV, and the ability to use various HCV strains within this system is important for future studies. In this study, we aimed to establish a novel HCV cell culture system using another HCV genotype 2a strain, J6CF, which replicates in chimpanzees but not in cultured cells. We identified an effective cell culture-adaptive mutation in NS4A and established a replication-competent J6CF strain in cultured cells with minimum essential modifications. The described strategy can be used in establishing a novel HCV cell culture system, and the replication-competent J6CF clone composed of the minimum essential modifications needed for cell culture adaptation will be valuable as another representative of genotype 2a strains.